Complete genome sequence of Oceanithermus profundus type strain (506T). Issue 2 (March 2011) - Pati, Amrita; Zhang, Xiaojing; Lapidus, Alla; Nolan, Matt; Lucas, Susan; Glavina Del Rio, Tijana; Tice, Hope; Cheng, Jan-Fang; Tapia, Roxane; Han, Cliff; Goodwin, Lynne; Pitluck, Sam; et al.
Abstract Oceanithermus profundus Miroshnichenkoet al. 2003 is the type species of the genusOceanithermus, which belongs to the familyThermaceae . The genus currently comprises two species whose members are thermophilic and are able to reduce sulfur compounds and nitrite. The organism is adapted to the salinity of sea water, is able to utilize a broad range of carbohydrates, some proteinaceous substrates, organic acids and alcohols. This is the first completed genome sequence of a member of the genusOceanithermus and the fourth sequence from the familyThermaceae . The 2, 439, 291 bp long genome with its 2, 391 protein-coding and 54 RNA genes consists of one chromosome and a 135, 351 bp long plasmid, and is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.